‘Space Weather Sentinels’: Halley and the evolution of geospace science - Oates, Alice E (The Royal Society, 2025)
Peer reviewed: True Publication status: Published The words ‘Antarctic science’ are often synonymous with dramatic, sublime images of penguins and frozen landscapes, but not all Antarctic science looks to the ice or its megafauna. While Antarctica is an important focus of scientific research in its own right, it is also a platform ideally suited to the pursuit of geophysical science—such as solar–terrestrial physics. Investigating the histories of these fields of science contributes not only to our understanding of the history of Antarctic science, but also to the evolution of Antarctic research stations as sites entangled in international networks of people and places beyond Earth's coldest continent. This paper presents the case of Halley VI research station, a British Antarctic Survey station on the Brunt Ice Shelf in East Antarctica, and its co-evolution with geospace science throughout the 1970s and 1980s. Halley's infrastructure and science shaped, and were shaped by, the evolution of geospace science in this period, via Halley's involvement in a series of international geospace collaborations. This co-evolution also affected how the British Antarctic Survey was able to respond to changing UK science policies in later decades. This case demonstrates that Antarctic stations, while physically remote, have historically been entangled in complex networks of people, politics and science that range far beyond Antarctica itself.